Glial functions in the blood-brain communication at the circumventricular organs - Miyata, Seiji (Frontiers in Neuroscience, 2022)
The circumventricular organs (CVOs) are located around the brain ventricles, lack a blood-brain barrier and sense blood-derived molecules. This review discusses recent advances in the importance of CVO functions, especially glial cells transferring periphery inflammation signals to the brain. The CVOs show size-limited vascular permeability, allowing the passage of molecules with molecular weight <10,000. This indicates that the lack of an endothelial cell barrier does not mean the free movement of blood-derived molecules into the CVO parenchyma. Astrocytes and tanycytes constitute a dense barrier at the distal CVO subdivision, preventing the free diffusion of blood-derived molecules into neighboring brain regions. Tanycytes in the CVOs mediate communication between cerebrospinal fluid and brain parenchyma via transcytosis. Microglia and macrophages of the CVOs are essential for transmitting peripheral information to other brain regions via toll-like receptor 2 (TLR2). Inhibition of TLR2 signaling or depletion of microglia and macrophages in the brain eliminates TLR2-dependent inflammatory responses. In contrast to TLR2, astrocytes and tanycytes in the CVOs of the brain are crucial for initiating lipopolysaccharide (LPS)-induced inflammatory responses via TLR4. Depletion of microglia and macrophages augments LPS-induced fever and chronic sickness responses. Microglia and macrophages in the CVOs are continuously activated, even under normal physiological conditions, as they exhibit activated morphology and express the M1/M2 marker proteins. Moreover, the microglial proliferation occurs in various regions, such as the hypothalamus, medulla oblongata, and telencephalon, with a marked increase in the CVOs, due to low-dose LPS administration, and after high-dose LPS administration, proliferation is seen in most brain regions, except for the cerebral cortex and hippocampus. A transient increase in the microglial population is beneficial during LPS-induced inflammation for attenuating sickness response. Transient receptor potential receptor vanilloid 1 expressed in astrocytes and tanycytes of the CVOs is responsible for thermoregulation upon exposure to a warm environment less than 37 °C. Alternatively, Nax expressed in astrocytes and tanycytes of the CVOs is crucial for maintaining body fluid homeostasis. Thus, recent findings indicate that glial cells in the brain CVOs are essential for initiating neuroinflammatory responses and maintaining body fluid and thermal homeostasis.